The German stock corporation act - Schneider, Hannes (Kluwer Law International, 1996)
This book contains an English translation of the German Stock Corporation Law. The English and German texts are synoptically arranged. The introduction provides a concise overview of the main elements of the law and facilitates an understanding of the complex statutory provisions for the English-speaking reader. The main characteristics of both types of stock corporations in Germany, the AG and the KGaA, are described and explained. Several legal aspects of stock corporations, such as their formation and management, shareholders, minority rights, capital, integration, and mergers are covered in this book. The index is also arranged in bi-lingual form. The book reflects the prevailing state of legislation and will prove valuable to foreign lawyers and business people dealing with stock corporations.